Military Sexual Assault in Transgender Veterans: Results From a Nationwide Survey. Issue 2 (30th March 2018) - Beckman, Kerry; Shipherd, Jillian; Simpson, Tracy; Lehavot, Keren
Abstract: There is limited understanding about the frequency of military sexual assault (MSA) in transgender veterans, characteristics associated with MSA, or subsequent mental and behavioral health problems. To address this gap, we used an online national survey of 221 transgender veterans to identify prevalence of MSA and to assess its association with demographic characteristics, past history of sexual victimization, and stigma‐related factors. We also evaluated the association between MSA and several mental and behavioral health problems. Overall, 17.2% of transgender veterans experienced MSA, but rates differed significantly between transgender women (15.2%) and transgender men (30.0%). Using adjusted regression models, MSA was associated with adult sexual assault prior to military service, odds ratio ( OR ) = 4.05, 95% CI [1.62, 10.08], and distal minority stress during military service, OR = 2.98, 95% CI [1.28, 6.91]. With respect to health outcomes, MSA was associated with past‐month posttraumatic stress disorder (PTSD) symptom severity, B = 10.18, 95% CI [3.45, 16.91]; current depression symptom severity, B = 3.71, 95% CI [1.11, 6.30]; and past‐year drug use, OR = 3.17, 95% CI [1.36, 7.40]. Results highlight the vulnerability of transgender veterans to MSA, and the need for military prevention programs that acknowledge transgender individuals' heightened risk. Furthermore, clinicians should consider clinical screening for PTSD, depression, and drug use in transgender veterans who have a history of MSA.